2014
DOI: 10.1002/chem.201303719
|View full text |Cite
|
Sign up to set email alerts
|

Tracking “Apolar” NMe4+ Ions within Two Polyoxothiomolybdates that Have the Same Pores: Smaller Clathrate and Larger Highly Porous Clusters in Action

Abstract: Two nanosized polyoxothiometalates were synthesized based on linking oxomolybdate building blocks with {Mo2O2S2}(2+) groups. Remarkably, both compounds are formed selectively primarily upon changing the related concentrations in a logical way; they exhibit common structural features based on the same {Mo9O6S3}-type pores, which result in connections between {Mo6O21} pentagons and {Mo2O2S2}(2+) linkers. Whereas the much larger spherical Mo132-type Keplerate contains twenty pores, the smaller Mo63 -type cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 73 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…Changing the nature of the pore from {Mo 9 O 9 } to {Mo 9 S 3 O 6 } leads to a drastic decrease of the stability constant from K S = 1550 ± 200 to 210 ± 20 while the main features of the capsule (ionic charge, size and shape) remain almost unchanged. 19 The rationale of such a result is the larger ionic radius of the sulfur atom which reduced the inner space of the pore and then increases the unfavorable steric effect for the NMe 4 + plugging. We tried to get Xray diffraction structural data to support these solution studies.…”
Section: Resultsmentioning
confidence: 99%
“…Changing the nature of the pore from {Mo 9 O 9 } to {Mo 9 S 3 O 6 } leads to a drastic decrease of the stability constant from K S = 1550 ± 200 to 210 ± 20 while the main features of the capsule (ionic charge, size and shape) remain almost unchanged. 19 The rationale of such a result is the larger ionic radius of the sulfur atom which reduced the inner space of the pore and then increases the unfavorable steric effect for the NMe 4 + plugging. We tried to get Xray diffraction structural data to support these solution studies.…”
Section: Resultsmentioning
confidence: 99%
“…Such an observation has been fully analyzed from an experimental and theoretical point of views in a recent report which demonstrates that specific interactions between the capsules and DMA + cations take place involving the twenty {Mo 6 O 9 } ether crown‐like pores of the capsule 30. Such specific interactions have been observed also in solution between the NMe 4 + ion and the sulfurated Keplerate [Mo 132 O 312 S 60 (H 2 O) 72 (CH 3 COO) 30 ] 42− 31. Such solution studies and related results correspond to complementary insights previously evidenced in the solid state and described as the pore plugging process 32…”
Section: Resultsmentioning
confidence: 99%
“…[83] In this case, the alkyl chain length is probably too small to get liquid crystals phase but they used it to prepare coassembly of spherical 6.2 nm maghemite (- ligands and higher charge. [33] The larger charge of the capsule allows associating more [82,84] with the permission from the Royal Society of Chemistry) 33represents an attractive system. [85] It possesses a large anionic pocket of about 1 nm in diameter, which is able to include various transition metals, a key step for the elaboration of efficient materials for magnetic, luminescent, catalytic or electrocatalytic properties.…”
Section: Pairing Poms With Non-mesogenic Cationsmentioning
confidence: 99%
“…The Linqvist structure [M 6 O 19 ] xand its derivatives (Figure 1) are probably the main archetypical structure of this class but in the domain of isopolyoxomolybdates, Müller et al opened a new field of investigation when they reported the discovery of a fullerene-like, all-inorganic hollow spheres containing 132 molybdenum centers in 1998 (Figure 1). [30] [21,[31][32][33] Not only aesthetic, these nanometric hollow clusters behave as functional nanoflasks for cations or molecules trapping, [34][35][36][37] catalysis [38] or specific chemical transformations. [39] This family of polyoxomolybdates was also complemented by other giant POMs namely the "big wheels" {Mo-154}, {Mo-176} and {Mo-248}, and the "blue lemon" {Mo-368}, which expanded the frontiers of inorganic chemistry to the mesoscopic world (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%